A Literatura Kafkiana como suporte narrativo em Resident Evil: Revelations 2 - CAVALCANTE, Antonia Karine do Nascimento Rosendo (2024)
The research explores the relationship between literature and video games, focusing on Franz Kafka's work and its adaptation in Resident Evil: Revelations 2, a 2015 game by Capcom. The study examines how Kafka's literary elements enrich the game's narrative, offering a deeper and more immersive experience for players. The research encompasses the inclusion of quotes, references to Kafka's characters and locations in the game, as well as drawings made by the writer. The adopted methodology includes a detailed analysis of the game and its elements in relation to Kafka's work, focusing on the interaction between literature and video games: how Kafka's works influence the narrative of Resident Evil: Revelations 2. Initially, the absurd element characteristic of Kafka and its relation to the survivor horror genre in games were investigated. The methodology allowed for a deep dive into three specific aspects: 1) quotes from Kafka's works during gameplay; 2) References to Franz Kafka's work through collectible items in the game's scenarios; 3) Kafka's works functioning as an element of the game itself through the character Alex Wesker. This multidimensional approach aimed to understand how literature can enrich and adapt to the context of video games, drawing from studies by Baumann (2008), Carone (2011), Vieira (2017), Martins (2021), among others. The research demonstrates that Kafka, with his absurd and surreal style, adapts well to the universe of games, particularly in the survival horror genre. Kafka's presence in the game is not just a literary homage but a strategy that adds layers of meaning to the player's experience. The study concludes that Kafka's literature was effectively adapted to enrich the narrative of Resident Evil: Revelations 2, as the adaptation not only offers a new perspective on Kafka's work but also illustrates the potential of literature to influence and enrich video games. The research significantly contributes to game studies and stimulates future research in the field.